Baseline Soluble Anti-erythropoietin Antibody Level Is an Independent Associated Factor for Follow-Up Erythropoietin Demand in Maintenance Dialysis Patients With End-Stage Renal Disease: A Prospective Cohort Study - Zhang, Ying; Bian, Shi-Zhu; Yang, Kun; Wang, Yiqing; Tang, Sha; Wang, Weili; Wang, Daihong; Nie, Ling; Zhao, Jinghong (Frontiers in Medicine, 2020)
Aims: The aim of this study was to identify the predictive role of baseline anti-erythropoietin (anti-EPO) antibody levels in follow-up EPO demand in maintenance dialysis patients with end-stage renal disease (ESRD). Methods: Baseline routine blood parameters, clinical data, dialysis-related parameters, EPO, anti-EPO antibody, and anti-EPO-receptor antibody were also measured. Differences in the abovementioned variables were compared among four intervals of the EPO demand index (EDI). Further univariate and adjusted logistic regression analyses were performed to identify the independent predictors for higher EPO demand. Results: The predialysis potassium ion concentration was significantly higher in the fourth quartile (Q4) population than in the other three populations (p < 0.05). Furthermore, the anti-EPO antibody level showed significant differences among the four intervals (p = 0.006). The baseline anti-EPO antibody level was correlated with the follow-up EDI (r2 = 0.0377, p = 0.030). Furthermore, the follow-up EDI was significantly higher in the anti-EPO antibody-positive group (p = 0.02). Age (OR = 1.071, p = 0.005), ferritin (OR = 1.001, p = 0.038), potassium ion concentration before dialysis (OR = 2.781, p = 0.012), dialysis duration (OR = 1.025, p = 0.030), and anti-EPO antibody level (OR = 7.694, p = 0.004) were potential predictors for higher EPO demand. After adjustment, age (OR = 1.072, p = 0.026), potassium ion concentration before dialysis (OR = 3.425, p = 0.013), and EPO level (OR = 5.27, p = 0.007) were independent predictors for higher EDI demand. Conclusion: The baseline anti-EPO antibody level combined with an older age and a higher predialysis potassium ion concentration are independent predictors for a higher follow-up EPO demand in maintenance dialysis patients with ESRD.